Cross Border E-Commerce: Tinjauan Pustaka Sistematis - Pambudi, Yustikarani Julianti; Priyadi, Dhisa Tania; Rahmawati, Anisa; Ratana, Dhany Surya (Jurnal Administrasi Bisnis, 2024)
Cross-border e-commerce continues to develop, opening boundaries between regions and countries in buying and selling transactions. The ease as a result of this technological development continues to make various parties strive to contribute. This research aims to identify research trends on CBEC topics, the development of the number of international publications on CBEC topics, the productivity of international publications on CBEC research, and the development of research topics in international publications on CBEC topics. A total of 190 articles were identified for further analysis using the bibliometric method. The results of this study obtained three main theme groups related to CBEC, namely CBEC technology, consumer behaviour and CBEC business processes.Cross border e-commerce terus berkembang membuka batas antar wilayah dan negara dalam melakukan transaksi jual beli. Kemudahan akibat dari perkembangan teknologi ini terus membuat berbagai pihak berupaya untuk berkontribusi. Penelitian ini bertujuan untuk mengidentifikasi tren penelitian pada topik CBEC, perkembangan jumlah publikasi internasional pada topik CBEC, produktivitas publikasi internasional pada penelitian CBEC, perkembangan topik penelitian pada publikasi internasional untuk topik CBEC. Sebanyak 190 artikel yang berhasil diidentifikasi untuk dianalisis lebih lanjut menggunakan metode bibliometrik. Hasil dari penelitian ini didapatkan tiga kelompok tema utama berkaitan dengan CBEC yaitu teknologi CBEC, perilaku konsumen dan proses bisnis CBEC.